Evaluating the effects of specialty protein sources on nursery pig performance - Jones, Aaron Michael (Kansas State University, 2017)
A total of 6,465 nursery pigs were used in 8 experiments. Experiment 1 investigated the effects of Lactobacillus plantarum (LP) or fermented soybean meal (FSBM) on nursery pig growth performance. A LP × FSBM interaction was detected for G:F, where LP and FSBM individually improved G:F, but the effect was not additive. Experiment 2 evaluated the effects of increasing levels of LP on nursery pig performance. No evidence for differences in growth performance were observed among dietary treatments. Experiment 3 and 4 examined the effects of fish meal source and level on nursery pig growth performance. Overall, a source × level interaction for ADG, G:F and final BW was observed as increasing fish meal source 1 improved ADG and G:F; however, pigs fed fish meal source 2 had improved ADG and G:F at 3%, but decreased at 6%. Pigs fed fish meal source 3 had no further improvements in ADG and G:F beyond the 3% inclusion. No evidence for differences were detected between the dietary treatments for ADFI. Experiment 5 evaluated the effects of feeding fish solubles on nursery pig performance. Pigs fed diets with fish meal had increased ADG and ADFI compared to pigs fed the control diet. There was no evidence for differences in growth performance as fish solubles increased. Experiment 6 and 7 investigated the effects of enzymatically-treated soybean meal (ESBM) on nursery pig performance. Results indicated that nursery pigs fed diets with greater than 9% of ESBM resulted in decreased ADFI and final BW. Experiment 8 evaluated the effects of dietary electrolyte balance (dEB) on nursery pig performance. Increasing dEB in diets from weaning to 21-d after weaning resulted in an increase in ADG and BW, which was the result of a marginally significant improvement in ADFI and G:F. Finally, an experiment was conducted to determine the optimal strategy for collecting and submitting samples that adequately describe the nutrient levels in diets collected from a commercial swine facility. Sampling feeders with a probe resulted in less variability on an individual basis, but seemed to get washed out when individual samples were pooled to form a composite sample.
Keywords: Enzymatically-treated soybean meal; Fermented soybean meal; Fish meal; Nursery pig; Sampling technique from feedersDietary electrolyte balance